Legal protection for doctors during the covid-19 pandemic review from civil law, criminal law, and law no 2009 concerning health - Fauziah, Faridatul; Mukhlis, Muchammad Fauzan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Covid-19 is a disease that can easily spread and infect anyone, including medical personnel. Handling COVID by health workers such as doctors, is faced with a dilemma because the disease itself is easy to transmit to other people. Doctors are a profession that is at the forefront of dealing directly with Covid-19. In conditions like this, doctors sometimes become victims/died in order to protect the public from the spread of the Covid-19 pandemic. This type of research is normative juridical with the main sources of legal material being the Civil Code and the Criminal Code and Law no. 36 of 2009 concerning Health. Law Number 36 of 2009 concerning Health Article 83 paragraph 2 states that the government guarantees legal protection for everyone according to their abilities. The importance of fulfilling the rights of doctors to be able to work accsording to medical standards. In the critical condition of the Covid-19 pandemic as it is today, the availability of PPE for doctors is one of the essential elements that must be met for doctors to fulfill the element of safety for doctors. In civil law, the doctor-patient relationship states that doctors in carrying out medical practice have the right to obtain complete, honest and clear information from patients or their families. health, then this can lead to criminal acts that are included in acts of persecution or crimes that endanger public safety for people.